Chronicles in teacher education: in search of joy in school - Fortunato, Ivan (2020)
This paper is an experience report produced from the final result of the discipline “School and Curriculum” of the teacher formation course, held in the second semester of 2019. The pedagogical work was conducted through chronicles, which were gathered in a digital book of free distribution. At the end, a balance of this work was carried out collectively, having been recognized that the reflection of the school daily life through the chronicles, in addition to the collective challenge of producing a book, became fundamental elements for the initial proposal to think (and live) the joy at school.